Analisis Perilaku Verbal Pemain Mobile Legends Berusia 13-17 Tahun secara Daring - Nur Aini Rakhmawati; Etria Sepwardhani Purba; Cita Engedi K; Venus Oktanada Gemilang; Renada Aulia Salsabila; Amir Mu’tashim Billah (Cakrawala - Jurnal Humaniora, 2020)
The purpose of this paper was to analyse online verbal behaviour related to the activities of online game players in the Mobile Legends game especially for children aged 13-17 years. As is commonly found many social media accounts of Mobile Legends players often upload streaming video games and many aggressive esxpressions are spoken or typed during the game. This research used qualitative methods by using players social media accounts as data soures. From these data source can be obtained about about the verbal behaviours of online game players gathered from their personal social media accounts. Based in the results of data analysis, most players often used aggressive verbal words when they feel dejected about other players or when the game’s atmosphere heated up or also if the players is ini an unfavorable condition during the game. This certainly has a bad impact on children because it can be a bad habit because they often used the words that are aggressive during playing the game.